Erratum: An Examination of the Use of the Framework of Social Marketing to Achieve Environmental Sustainability in International Agricultural and Extension Education - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Warner, L. A., & Murphrey, T. P. (2015). An Examination of the Use of the Framework of Social Marketing to Achieve Environmental Sustainability in International Agricultural and Extension Education. Journal of International Agricultural and Extension Education, 22(2), 20-36.” was incorrect as published. The correct DOI is: 10.4148/2831-5960.1263